Eingeorenenkirchen in Süd- und Südwestafrika: ihre Geschichte un Sozialstruktur [Native churches in S. and S. W. Africa: Their history and social structure] - Schlosser, Katesa (W. G. Mühlau, 1958)
Chapters on Nicholas B. H. Bhengu, Cecil Hector of Independent Lutheran Mission Church of South Africa; Prophets Mgijima, Lekganyane, and Shembe.